Baseline characteristics of depressive disorders in Thai outpatients: Findings from the Thai Study of Affective Disorders - Tinakon Wongpakaran (2018)
Background: The Thai Study of Affective Disorders was a tertiary hospital-based cohort study developed to identify treatment outcomes among depressed patients and the variables involved. In this study, we examined the baseline characteristics of these depressed patients. Methods: Patients were investigated at eleven psychiatric outpatient clinics at tertiary hospitals for the presence of unipolar depressive disorders, as diagnosed by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition. The severity of any depression found was measured using the Clinical Global Impression and 17-item Hamilton Depression Rating Scale (HAMD) clinician-rated tools, with the Thai Depression Inventory (a self-rated instrument) administered alongside them. Sociodemographic and psychosocial variables were collected, and quality of life was also captured using the health-related quality of life (SF-36v2), EuroQoL (EQ-5D), and visual analog scale (EQ VAS) tools. Results: A total of 371 outpatients suffering new or recurrent episodes were recruited. The mean age of the group was 45.7±15.9 (range 18-83) years, and 75% of the group was female. In terms of diagnosis, 88% had major depressive disorder, 12% had dysthymic disorder, and 50% had a combination of both major depressive disorder and dysthymic disorder. The mean (standard deviation) scores for the HAMD, Clinical Global Impression, and Thai Depression Inventory were 24.2±6.4, 4.47±1.1, and 51.51±0.2, respectively. Sixty-two percent had suicidal tendencies, while 11% had a family history of depression. Of the major depressive disorder cases, 61% had experienced a first episode. The SF-36v2 component scores ranged from 25 to 56, while the mean (standard deviation) of the EQ-5D was 0.50±0.22 and that of the EQ VAS was 53.79±21.3. Conclusion: This study provides an overview of the sociodemographic and psychosocial characteristics of patients with new or recurrent episodes of unipolar depressive disorders. © 2014 Wongpakaran et al.